Outbreak of Paracoccus marginatus in Bangladesh and its control strategies in the fields - Khan, MAM; Biswas, MJH; Ahmed, KS; Sheheli, S (Progressive Agriculture, 2015)
A field survey as well as market survey on Papaya mealybug, Paracoccus marginatus (Williams and Granara de Willink) was conducted in different regions of Bangladesh to know the infestation level, economic loss, and common management practices used by farmers to control this insect. Field survey revealed that more than one third of the papaya plants were affected by papaya mealybug and papaya growers faced a great economic loss. Severe infestation of papaya mealybug was also found in the nurseries of the survey areas. Market survey indicated that the retailers faced difficulties to sell infested papaya fruit. Seven plants other than papaya were recorded to which papaya mealybug also attacked. The plants were Hog plum (Sponolia spinnata), Chili (Capsicum frutescence), Okra (Abelmoscus esculentus), Brinjal (Solanum melongena), Guava (Psidium melongena), Velvet-apple (Diospyros blancoi) and Hibiscus (Hibiscus rosa-scinensis). The farmers of the survey area used several chemical insecticides indiscriminately against the papaya mealybug and did not get satisfactory control. Some indigenous pest management tactics were also used against papaya mealybug including the use of wood ash and bark extract of mahogany tree. Progress. Agric. 2014. 25: 17-22